2015
DOI: 10.1155/2015/987358
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Urban Multicriteria Shortest Path Stochastic Optimization Algorithm

Abstract: Drivers’ route choice behavior is usually personalized and multicriteria in practice. Therefore, the urban shortest path problem is the personalized urban multicriteria shortest path (PUMSP) problem. However, the solutions of the PUMSP problem are difficult to meet the drivers’ travel habits in the state of the art. To solve this problem, first, a new stochastic optimization algorithm based on the iterative calculation of a valid route set is proposed in this paper. The effective and reasonable path searching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For this purpose literature review is performed. On the basis of this review, several parameters required for the optimal path as identified like travel time, travel distance, toll on route, quantitative information, qualitative information, number of turns, weather, time of day, congestion, safety, directness and comfort (Bowen and Ciyun, 2015 ;Li and Leung, 2011;Musliman, Rahman, and Coors, 2007;Papinski and Scott, 2011). However, in a rural area, some of these parameters are not required.…”
Section: Least Cost Optimal Pathmentioning
confidence: 99%
“…For this purpose literature review is performed. On the basis of this review, several parameters required for the optimal path as identified like travel time, travel distance, toll on route, quantitative information, qualitative information, number of turns, weather, time of day, congestion, safety, directness and comfort (Bowen and Ciyun, 2015 ;Li and Leung, 2011;Musliman, Rahman, and Coors, 2007;Papinski and Scott, 2011). However, in a rural area, some of these parameters are not required.…”
Section: Least Cost Optimal Pathmentioning
confidence: 99%
“…Designed algorithm with transfer delaying is based on exact label correcting algorithm, and effectiveness of the algorithm are tested on computing examples. Bowen and Ciyun [13] propose stochastic optimization approach based on iterative calculation of a valid route set for solving personalized urban multicriteria SPP. Results of the proposed approach are compared with genetic algorithm, and it is efficient and successful to solve the problem.…”
Section: Introductionmentioning
confidence: 99%